Effectiveness of Supervision Implementation in Educational Institutions - Lisa Hepriyanti; Rahma Rahma; Astri Astri; Serli Widia Astuti; Kasinyo Harto; Choirun Niswah (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Supervision is carried out as an effort by people in authority in the world of education to supervise everything done by people related to the world of education, be it teachers, students, and so on. This paper aims to discuss the effectiveness of the implementation of supervision, with the method used is a literature review or literature study that contains theories relevant to the problems to be discussed, and the study describes the concepts and theories used based on the available literature, from books and articles that have been published in scientific journals. Supervision is carried out to find out what happens in an educational institution, such as if there is an inequality or problem in an educational institution, and the best way will be found to overcome the problem. This is an example of one of the importance of supervision. The effectiveness of the implementation of supervision will be carried out if it has gone through the planning stage, which, of course, has been mutually agreed upon by the people in charge in the world of education, so supervision is carried out in a directed and measurable manner by the agreed provisions to achieve the goals that have been expected together.